Durability of pulmonary vein isolation following cryoballoon ablation: lessons from a large series of repeat ablation procedures. (19th May 2022) - Mugnai, G; Cecchini, F; Stroker, E; Sieira, J; Bolzan, B; Tomasi, L; Brugada, P; De Asmundis, C; Chierchia, GB
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The cryoballoon technology has been widely proven to be effective in achieving acute pulmonary vein (PV) isolation and favorable clinical outcome. To date, little information is still available about occurrence of late PV reconnection after cryoballoon ablation. Purpose: To assess the rate of durable PV isolation following cryoballoon ablation of atrial fibrillation in the setting of repeat procedures. Methods and Results: A total of 154 consecutive patients (90 male, 58.4%; mean age 60.6±12.6 years) underwent a repeat procedure, after a mean 21.5±12.4 months (median 14 months), after index ablation using the 28-mm second-generation cryoballoon. All repeat ablations were performed using a 3-dimensional electro-anatomical mapping system. Among all 590 PVs, including 26 left common ostiums (LCOs), 99 (16.8%) showed a PV reconnection in 86 patients (1.15 per patient). Persistent PV isolation could be documented in 491 of 590 PVs (83.2%). In 68 of 154 patients (44%), all PVs were electrically isolated. In the multivariable analysis, balloon nadir temperature (p<0.01) and time to PV isolation (P=0.02) independently predicted late PV reconnection. Conclusions: The rate of late PV reconnection after second-generation cryoballoon ablation was low (1.15 PVs/patient). Globally, the rate of durable PV isolation assessed during repeat procedures was 83.2%. The balloon nadir temperature and faster time to isolation were independently associated with durable PV isolation.